Use of express tests in the practice of family doctors and pediatricians - Liudmyla Gospodarenko; Tetiana Klets; Ganna Gnyloskurenko; Roman Terletskyi; Diana Kononenko (Bogomolets National Medical University, 2021)
Rapid diagnosis significantly reduces the patient's expectation of effective medical care. As a result, rapid or POC-tests are becoming increasingly important in the world. However, the frequency of their use, the availability of tests in medical facilities, the awareness of physicians about diagnostic capabilities and the need for them are currently unclear. The aim of our study was to determine the level of awareness of physicians about the use of rapid tests for influenza, RS-virus, ꞵ-hemolytic group A streptococcus  and laboratory markers of inflammation in the form of POC-tests in daily practice. The study was conducted by interviewing 78 pediatricians and family physicians in Kyiv and Kyiv region who work at the primary and secondary levels of medical care. A questionnaire from EAPRASnetT (European Academy of Pediatric Research in the network of outpatient settings) was used for the survey. Our research has shown that hospital physicians are more informed about the use of rapid diagnostics and are more willing to use it in the treatment and diagnostic process. A rapid antigen test for influenza is available to the vast majority of inpatients (78%) and only half of outpatients (46.3%). Half of primary care physicians (56.1%) and the vast majority of secondary care professionals (73%) are willing to use this test in practice if it is available. The results of our study also showed a higher adherence to this rapid test of inpatients, as only 2.7% of them would like to confirm the results of POC-tests by laboratory tests (compared to 22% of outpatients). Most doctors in both outpatient clinics (61%) and inpatients (75.7%) are ready to use a rapid test for respiratory syncytial virus. Only 2.7% of hospital doctors would like to have a laboratory version, and outpatients would be completely satisfied with a quick test. However, due to the lack of trust in 14.6% of cases, they would like to confirm its results by laboratory testing. About a third of physicians (39%) use the rapid test for ꞵ-hemolytic group A streptococcus in the outpatient clinic, but half (51.2%) stated the need for this test and its unavailability. In the hospital, the data obtained were the opposite: half of doctors already use this test (59.5%), and another third would like to have it (35.1%). Rapid C-reactive protein testing is poorly used by physicians in both health care settings (12.2% in the outpatient setting and 29.7% in the inpatient setting) due to low security and lack of awareness. This is confirmed by the fact that 75.6% of primary and 64.9% of secondary care physicians stated that the test is not available, but they are ready to use this test if available. POC-test for C-reactive protein is used more in the hospital than in the outpatient clinic. At the outpatient stage, 12.2% of physicians do not consider it appropriate to use C-reactive protein in the diagnosis of diseases, in the hospital of such physicians 5%. About 10% of doctors in both groups expressed distrust in the rapid CRP-test, as they would like to use only the laboratory version. Doubts about the accuracy of almost twice as many outpatients, as more often would like to check it with a laboratory version (19.5% vs. 10.8% of inpatients). Therefore, one in five physicians in the outpatient clinic would use both the laboratory and POC versions. The rapid test for procalcitonin is used by every 5th doctor in the hospital and only 7% of the primary care, which can be attributed to the low availability of the test in medical practice, poor provision of medical institutions with POC-tests, as 62.2% and 78% of doctors the hospital and the clinic replied that they would use it if it was available. As for the complete general analysis of blood with leukocyte formula, only 17.1% and 35.5% of doctors of the polyclinic and hospital would like to use its POC version. Interviewed physicians would prefer a laboratory version of the test.It is necessary to raise awareness of physicians, especially primary care, about modern diagnostic methods, namely the practice of POC-tests and make them more accessible, which would significantly improve the diagnosis and treatment of patients, would have a positive impact on public health and significant economic effect.